Longevity Shocks with Age-Dependent Productivity Growth - Ben J. Heijdra; Laurie S. M. Reijnders (Center for Economic Studies and ifo Institute (CESifo), 2015)
The aim of this paper is to study the long-run effects of a longevity increase on individual decisions about education and retirement, taking macroeconomic repercussions through endogenous factor prices and the pension system into account. We build a model of a closed economy inhabited by overlapping generations of finitely-lived individuals whose labour productivity depends on their age through the build-up of labour market experience and the depreciation of human capital. We make two contributions to the literature on the macroeconomics of population ageing. First we show that it is important to recognize that a longer life need not imply a more productive life and that this matters for the affordability of an unfunded pension system. Second, we find that factor prices could move in a direction opposite to the one accepted as conventional wisdom following an increase in longevity, depending on the corresponding change in the age-productivity profile.
Keywords: E20; D91; I25; J11; J24; J26; 330; demography; education; retirement; human capital